Assessment of Water Pollution in Tipparthy Revenue Sub-Division, Nalgonda (District), Andhra Pradesh, India - Medikondu Kishore; Y. Hanumantharao (E-Journal of Chemistry)
A systematic study has been carried out to explore the physicochemical characteristics of drinking water sources of Tipparthy revenue sub-division, Nalgonda (District), Andhra Pradesh, India. Totally 49 water samples were collected from the different locations (22 villages) of the study area including bore well, open well and hand pump water and analyzed for pH, EC, TDS, turbidity, total hardness, fluoride, chloride, nitrate, nitrite, sulphate, phosphates, calcium, magnesium, sodium, potassium, Iron and dissolved oxygen. On an average, in almost all the samples, one or the other chemical constituent was beyond the permissible limits it was also concluded that water sources in the study area not fit for potability. Sodium absorption ratio (SAR) and water quality (WQI) studies indicate water available from all sources not fit for irrigation also. The study indicates the need for periodic monitoring of ground water in the study area.